Wade Keyes, The Code of Alabama, 1876: with References to the Decisions of the Supreme Court of the State upon the Construction of the Statutes; and in Which the General and Permanent Acts of the Session of 1876-7 have been Incorporated (1877) Page 989 § 4809 - (:unkn) unknown (General Publisher, 1877)
Indictments of concealed carry are sufficiently charged as concealed carry of a pistol, other firearm, Bowie-knife, or other knife or instrument of like description. Also required the defendant to bear the burden of proving a "legal excuse."
--
Keywords: CARRY - CONCEALED